The Interference of Maanyanese Language on English Pronunciation: A Case Study of University Students at Palangka Raya - Sonia Vriska Yulinda Jami; Maida Norahmi; Dellis Pratika; Sunanda Alam Muliawan; Hikmal Maulana Nasution (Asosiasi Dosen Perguruan Tinggi Islam, 2026)
Phonological interference from learners' first language (L1) is a well-established factor affecting English pronunciation, yet empirical research on L1 transfer among speakers of minority languages in Indonesia, particularly Maanyanese remains scarce. Despite growing interest in L2 phonology, no previous study has examined how the Maanyanese language, with its limited vowel inventory and absence of central vowels, influences English vowel production. This study addresses that gap by analyzing the English pronunciations of three Maanyanese-speaking university students selected through purposive sampling. Using a qualitative case study design, supported by semi-structured interviews and acoustic-phonetic analysis in Praat, the research investigated how learners produced English vowels that lack direct Maanyanese equivalents. The findings reveal systematic substitution patterns such as /I/->/i/, /V/->/a/ or /u/, and the consistent avoidance of schwa, indicating predictable L1 transfer. Interpreted through the Perceptual Assimilation Model, these patterns illustrate how unfamiliar L2 vowels are assimilated into existing Maanyanese phonemic categories, shaping learners' interlanguage phonology. Scientifically, the study contributes new evidence on L1 influence from an under-documented Indonesian language, expanding the understanding of L2 vowel acquisition in multilingual contexts. Pedagogically, the results underscore the need for explicit instruction in vowel reduction, tense-lax distinctions, and segmental contrasts not present in Maanyanese.